STUDY ON CONSUMER ACCEPTANCE OF SALTY DRY SQUID (Loligo sp.) NUGGET - Muhammad Zulhendri; Dewita Buchari; Suparmi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was aim to determine the level of consumer acceptance of salty dry squid nugget. About 4,2 kilograms of salty dry squid which obtained from Tanjungpinang market were processed into nugget. There were three kinds of nugget which made from meat of salty dry squid (200 grams; 300 grams and 400 grams) and other ingredients such as; tapioca flour, salt, sugar, egg, garlic, pepper, corn starch and bread crumbs. The parameter of this research was organoleptic assay (consumer acceptance) chemical analysis. The result showed that 200 grams of salty dry squid nugget was the best great meat and most fafourable by consumer acceptance with appearance 93.75%, aroma 72.50%, taste 71.25%, texture 95.00%, masture content 29.19%, protein content 16.22%, ash content 1.42%, fat content 4,31% and carbohydrat content 48,86 %.Keywords: Consumer acceptance, Nugget, Salty dry squid